Integrating a Process-Based Composite Application With ERP - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2011)
Using the Expense Claims Process, we describe howprocess based composite application can be integrated with ERP.The composite application leverages existing ERP functionalityby invoking enterprise services. The application is implementedusing SAP Netweaver Composition Environment and SAP ERP.